2008
DOI: 10.1002/jms.1454
|View full text |Cite
|
Sign up to set email alerts
|

Halohydrination of epoxy resins using sodium halides as cationizing agents in MALDI‐MS and DIOS‐MS

Abstract: Halohydrination of epoxy resins using sodium halides as cationizing agents in matrix-assisted laser desorption/ionization (MALDI) and desorption ionization on porous silicon mass spectrometry (DIOS-MS) were investigated. Different mass spectra were observed when NaClO(4) and NaI were used as the cationizing agents at the highest concentration of 10.0 mM, which is much higher than that normally used in MALDI-MS. MALDI mass spectra of epoxy resins using NaI revealed iodohydrination to occur as epoxy functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…They showed that the sensitivity and molecular weight distribution (MWD) is comparable to MALDI mass spectra obtained with the 2,5-dihydroxybenzoic acid (2,5-DHB) matrix. The same group investigated the halohydrination of epoxy resins using sodium halides as cationizing agents in MALDI and desorption ionization on porous silicon (DIOS) MS. With the use of deuterated methanol as the solvent, it was shown that the hydrogen atom source was probably ambient water or residual solvent, rather than being derived from matrixes . Another way of obtaining homogeneous sample preparations could be the miniaturization of sample spots , .…”
Section: New Aspects In Traditional Techniques and Principlesmentioning
confidence: 99%
“…They showed that the sensitivity and molecular weight distribution (MWD) is comparable to MALDI mass spectra obtained with the 2,5-dihydroxybenzoic acid (2,5-DHB) matrix. The same group investigated the halohydrination of epoxy resins using sodium halides as cationizing agents in MALDI and desorption ionization on porous silicon (DIOS) MS. With the use of deuterated methanol as the solvent, it was shown that the hydrogen atom source was probably ambient water or residual solvent, rather than being derived from matrixes . Another way of obtaining homogeneous sample preparations could be the miniaturization of sample spots , .…”
Section: New Aspects In Traditional Techniques and Principlesmentioning
confidence: 99%
“…Halohydrination of epoxy resin has been observed when some halogenated sodium salts (NaI and NaBr) have been used as cationizing agents. This halohydrination is not seen with NaCl because chlorine is less nucleophilic than bromine or iodine 62. For polymers that are not easily ionizable, it may be necessary to chemically derivatized them prior to measurement 63–65.…”
Section: Mass Spectrometry In Polymer Chemistrymentioning
confidence: 99%